Developing inclusive teacher education: A Stakeholder-driven feasibility study of ECE and SNED micro-credentials - Quileste, Ronald M. (CV. Yudhistt Fateeh, 2025)
This mixed-methods study examines the feasibility of implementing stackable micro-credential programs in Early Childhood Education (ECE) and Special Needs Education (SNED) at a Philippine university, responding to critical gaps in accessible teacher training. Combining needs assessment surveys (N=60), key informant interviews (n=10), and benchmarking of five leading universities, the research reveals strong demand for flexible upskilling, with 90% enrollment willingness and 65% preference for Master's-credit-bearing certificates. Stakeholders prioritized hybrid delivery (55% online, 37% blended), affordable pricing (₱20,000-25,000/ 350-440), and practical competencies like IEP design and play-based pedagogy. Benchmarking identified successful models integrating practicum requirements and ICT-enabled instruction, while institutional capacity analysis highlighted faculty readiness (5 qualified instructors) despite needing adjunct support for SNED supervision. Financial projections indicate sustainability, with Year 1 revenue (₱1.125M/ 19,500) exceeding operational costs by 125%. The study contributes to global conversations on micro-credentials by: (1) demonstrating their viability in resource-constrained contexts, (2) proposing a stakeholder-driven design framework adaptable to Global South institutions, and (3) addressing SDG4 targets for inclusive teacher training. Findings offer evidence for policymakers navigating the tension between standardization and localization in competency-based education reforms, particularly in Southeast Asia's evolving qualification landscapes.